2014
DOI: 10.1002/humu.22541
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Approach for Blind Detection of Balanced Chromosomal Rearrangements with Whole-Genome Low-Coverage Sequencing

Abstract: Balanced chromosomal rearrangement (or balanced chromosome abnormality, BCA) is a common chromosomal structural variation. Next-generation sequencing has been reported to detect BCA-associated breakpoints with the aid of karyotyping. However, the complications associated with this approach and the requirement for cytogenetics information has limited its application. Here, we provide a whole-genome low-coverage sequencing approach to detect BCA events independent of knowing the affected regions and with low fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(125 citation statements)
references
References 29 publications
3
121
0
1
Order By: Relevance
“…Next-generation sequencing has been reported to detect Balanced chromosomal rearrangement (BCA)-associated breakpoints with the aid of karyotyping. More recently, research reports demonstrated that low-coverage whole-genome sequencing has been applied to characterize chromosome structural variations with a high resolution, using different sequencing platform [28-31]. Our study results proved low-coverage whole-genome sequencing possesses significant advantages over conventional cytogenetic techniques once again.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Next-generation sequencing has been reported to detect Balanced chromosomal rearrangement (BCA)-associated breakpoints with the aid of karyotyping. More recently, research reports demonstrated that low-coverage whole-genome sequencing has been applied to characterize chromosome structural variations with a high resolution, using different sequencing platform [28-31]. Our study results proved low-coverage whole-genome sequencing possesses significant advantages over conventional cytogenetic techniques once again.…”
Section: Discussionsupporting
confidence: 57%
“…DNA samples from the proband, proband's younger brother and their parents were tested using a whole genome low-coverage paired-end NGS as described previously [32, 33]. …”
Section: Methodsmentioning
confidence: 99%
“…The library concentration was measured by quantitative PCR, and libraries with index tags were sequenced by Illumina HiSeq 2000 platform. Data analysis was performed through the following steps: (1) removal of the reads of adaptors and low-quality reads; (2) alignment of the reads to hg19 or GRCh37.1; and (3) translocation discovery, chimeric read-pair inputs for T-CHR (an in-house software [10]), analysis of clustering by locations, removal of PCR duplicates, and four steps of filtration [10]. …”
Section: Methodsmentioning
confidence: 99%
“…These are very low numbers compared with approximately 28 998 tests and 258 laboratories available in the United States. It is partly due to under-reporting as some laboratories in China such as the Shenzhen Birth Defect Screening Project Lab (Dong et al 2014) are not included on the list.…”
Section: Integrated Genetic/genomics Services In Hong Kong Taiwan Anmentioning
confidence: 99%